Thin endometrium is associated with higher risks of preterm birth and low birth weight after frozen single blastocyst transfer - Zheng, Yu; Chen, Biao; Dai, Jun; Xu, Bei; Ai, Jihui; Jin, Lei; Dong, Xiyuan (Frontiers in Endocrinology, 2022)
Background: It has been demonstrated that a thin endometrium is associated with a lower chance of pregnancy, but there is a paucity of research into whether a thin endometrium adversely affects perinatal outcomes. Methods: This was a retrospective cohort study on 10098 frozen cycles with single blastocyst transfer, resulting in 5505 singleton clinical pregnancies, and 4314 singleton live births. Patients were divided into a thin endometrium group (<8 mm) and a normal endometrium group (≥8 mm). Multivariable logistic regression with restricted cubic splines, receiver operating characteristic curve, and multivariable linear model were used for statistical analysis. Results: The incidences of preterm birth (15.65 vs. 9.80%, aOR=1.69 [1.19-2.42]), low birth weight (8.40 vs. 4.10%, aOR=2.05 [1.27-3.30]) and gestational diabetes (6.87 vs. 4.17%, aOR=1.74 [1.05-2.90]) were all higher in the endometrial thickness (EMT) <8 mm group. The miscarriage rate was higher in the EMT <8 mm group than the EMT ≥8 mm group (27.91 vs. 20.39%, aOR=1.40 [1.10-1.79]). Conclusion: A thin endometrium may be associated with a higher incidence of preterm birth, low birth weight, and miscarriage. Therefore, embryo transfer should be performed with caution in these patients, and postponing to a later cycle with a thicker endometrium should be considered.